Impact of recreational cannabis legalization on cannabis use, other substance use, and drug‐related offending among justice‐system‐involved youth. (23rd April 2022) - Kan, Emily; Beardslee, Jordan; Steinberg, Laurence; Frick, Paul J.; Cauffman, Elizabeth
Abstract: The present study assessed whether cannabis use, other types of substance use, and drug‐related offending changed among 1216 justice‐system‐involved youth after recreational cannabis legalization. Using generalized estimating equation population‐averaged models, we compared youth in California, where recreational cannabis is legalized, and Pennsylvania, where recreational use is still prohibited. Results indicated that cannabis use, cannabis selling, and driving under the influences (DUIs) increased more among Pennsylvanian than Californian youth. We found no changes in alcohol or noncannabis drug use after legalization. Cigarette use did not change significantly among Pennsylvanian youth, but Californian youth exhibited decreased cigarette use after legalization. Although not directly tested in the present analysis, it is possible that changes in state‐level recreational cannabis policies throughout the U.S. may contribute to more permissive attitudes toward cannabis, which leads to higher use and use‐related outcomes. Future research should continue to consider the potential impacts of legalization on other types of risky and illegal behavior.